(untitled) (Global Journal of Human-Social Science, 2022)
The purpose of the article is to highlight the stages of Jiří Kylián’s ballet master activity and its influence on the development of choreographic art of the postmodern era. Research methodology. Analysis, synthesis, generalization, systematization, which were used to determine the state of the problem, identification of biographical information, characteristics of the choreographer’s activity of Jiří Kylián; biographical method, which contributed to the study of creative activity of the choreographer; historical-genetic analysis and the method of periodization, which allowed to consider the problem of research in the time continuum and to distinguish four stages of choreographer-philosopher’s ballet master activity and find out the features of style, choreographic language at each stage. Scientific novelty.